PERMINTAAN KONTAINER UNTUK EKSPOR BARANG PADA PT. ARPENI PRATAMA OCEAN LINE TBK CABANG SEMARANG - Nadia Amanta Reisa; Karnowahadi - Karnowahadi; Paniya - Paniya (Politeknik Negeri Semarang, 2016)
International trade activities are export andimport. Exports are sending goods out ofIndonesian customs areas to be sent abroad.Delivery process of export goods, especiallyby sea is most widely performed usingcontainers. Container is a specially designedpackaging of a certain size. Seller or buyershould pay the Net Freight to the shippingcompany as the cost for shipping their goods.The results of this study indicate that: (1)Shipper I; the number of containers for exportgoods demand were significantly influencedby the net of freight, port of destinations,additional costs, and size of containers used,(2) Shipper II; significantly affected by netfreight and port of destination, (3) ShipperIII; significantly affected by net freight andport of destination, (4) Shipper IV and VI;significantly influenced by the net of freight,port of destination, and size of containersused, (5) Shipper V; significantly affected bynet freight. Overall (Shipper I - VI), it isconcluded that the total of demand forcontainers for exporting goods is significantlyaffected by net freight and port of destination.There were 54 port of destination withregularly sent the goods to Los Angeles, NewYork, and Houston. Overall the shipper usedGeneral Purpose Container size 20’DC,40’DC, 40’HC, and 45’DC.